2020
DOI: 10.1039/d0nr04520a
|View full text |Cite
|
Sign up to set email alerts
|

Targeted ferritin nanoparticle encapsulating CpG oligodeoxynucleotides induces tumor-associated macrophage M2 phenotype polarization into M1 phenotype and inhibits tumor growth

Abstract: Tumor-associated macrophages (TAM) are primarily of the M2 type that facilitates tumor growth, metastasis, and immunosuppression. Therefore, repolarizing the TAMs to the pro-inflammatory M1 type is a promising therapeutic strategy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…In addition, other nanoparticulate CpG oligodeoxynucleotides delivered into immunosuppressive TAMs and repolarized TAMs to immunogenic M1 phenotype and exhibited anti‐tumor effects in mice models. The reversal of phenotype of cultured human macrophages was also demonstrated in vitro 96 . These studies suggest that immunotherapy combined with nanoparticulate CpG oligodeoxynucleotides are a promising strategy to achieve a major breakthrough in immunosuppressive PDAC treatment.…”
Section: Targeting Immunosuppressive Barriers In the Tumor Microenvironmentmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, other nanoparticulate CpG oligodeoxynucleotides delivered into immunosuppressive TAMs and repolarized TAMs to immunogenic M1 phenotype and exhibited anti‐tumor effects in mice models. The reversal of phenotype of cultured human macrophages was also demonstrated in vitro 96 . These studies suggest that immunotherapy combined with nanoparticulate CpG oligodeoxynucleotides are a promising strategy to achieve a major breakthrough in immunosuppressive PDAC treatment.…”
Section: Targeting Immunosuppressive Barriers In the Tumor Microenvironmentmentioning
confidence: 65%
“…The reversal of phenotype of cultured human macrophages was also demonstrated in vitro. 96 These studies suggest that immunotherapy combined with nanoparticulate CpG oligodeoxynucleotides are a promising strategy to achieve a major breakthrough in immunosuppressive PDAC treatment.…”
Section: Vaccine Adjuvantsmentioning
confidence: 99%
“…From this perspective, E2-ferritin nanocage vaccines are proven to be safe and are worth promoting. Infectious viral pathogen-interrelated nanovaccines and self-assembling ferritin nanocages are also being developed in therapeutic anticancer nanomedicines, such as a targeted ferritin nanoparticle that inhibits tumor growth via a novel cancer immunotherapy strategy of encapsulating CpG oligodeoxynucleotides [33].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also suggested the use of TLR7 and TLR8 agonists to induce the activation of NF-κB to enhance immunotherapy efficacy and to increase TNF-α and IL-6 secretion [ 129 ]. For example, Shan et al used human ferritin heavy chain nanocages modified with M2pep to deliver a TLR agonist in a murine breast cancer model [ 116 ]. TLR agonist triggered TLR signaling and polarized TAM into M1 inflammatory macrophages [ 116 ].…”
Section: Nanoparticles To Target and Treat Tumour-associated Macrophagesmentioning
confidence: 99%
“…For example, Shan et al used human ferritin heavy chain nanocages modified with M2pep to deliver a TLR agonist in a murine breast cancer model [ 116 ]. TLR agonist triggered TLR signaling and polarized TAM into M1 inflammatory macrophages [ 116 ].…”
Section: Nanoparticles To Target and Treat Tumour-associated Macrophagesmentioning
confidence: 99%